The characteristics and helium generation potential of helium source rocks in the northern Ordos Basin, China - Ding, Zhengang; Liu, Chenglin; Chen, Jianfa; Wang, Haidong; Khan, Muhammad Aslam; Tian, Anqi (Frontiers in Earth Science, 2025)
The origin of helium is predominantly governed by helium source rocks, which encompass a spectrum of lithologies, including metamorphic rocks within the basin’s basement, and mudstones, coal, and other rocks in the overlying sedimentary formations. This study investigated four distinct types of potential helium source rocks and their associated helium generation potential within the northern Ordos Basin. Employing methodologies such as geological field surveys, interpretation of gravity and magnetic data, core descriptions, and analytical assays of major and trace elements, the study revealed the following: The Archean continental block in the northern Ordos Basin is overlain by a Paleoproterozoic metamorphosed volcano-sedimentary sequence, predominantly consisting of high-grade metamorphic gneisses, granulites, marbles, migmatites, and granitic gneisses. These rocks exhibit average uranium (U) and thorium (Th) abundances of 2.59 μg/g and 15.20 μg/g, respectively, and a helium generation intensity of 0.750 × 10−6 cm3/(Ma·g). The Mesoproterozoic Changcheng Series of metasedimentary rocks, distributed in parts of the central and northern basin, displays average abundances of U and Th at 2.66 μg/g and 8.36 μg/g, respectively, with a helium generation intensity of 0.562 × 10−6 cm3/(Ma·g). Widespread Upper Paleozoic Carboniferous-Permian mudstones and coal across the northern basin exhibit higher helium generation intensities. The mudstones of Taiyuan Formation have average U and Th abundances of 6.43 μg/g and 20.32 μg/g, respectively, and a helium generation intensity of 1.361 × 10−6 cm3/(Ma·g). In contrast, the coal from the Taiyuan Formation has average U and Th abundances of 5.61 μg/g and 13.09 μg/g, respectively, with a helium generation intensity of 1.054 × 10−6 cm3/(Ma·g). The research has established a classification criterion for crustal helium source rocks. According to the helium generation potential evaluation and identification chart for helium source rocks, Type Ⅰ helium source rocks are mainly granites and metamorphic rocks in the basement of the northern Ordos Basin and the Lvliang Mountains area on the eastern margin. The Hangjingi area in the northern Ordos Basin exhibits dual development of Archean-Paleoproterozoic basement-type and Upper Paleozoic sedimentary-type helium source rocks, characterized by a “multi-source helium supply” system, demonstrating significant helium source rock potential.